1998
DOI: 10.1161/01.hyp.31.1.480
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Pathways Mediate the Cardiovascular and Behavioral Responses to Substance P in the Rat Brain

Abstract: Abstract-Stlmulatlon of bram penventncular and hypothalamic substance P receptors mduces a pressor response and tachycardla associated with mesentenc and renal vasoconstrlctlon and hmdhmb vasodllatlon resembhng thus the classical defense reaction This cardiovascular response 1s brought about by the activation of the sympathoadrenal system and 1s accompanied by groommg behavior To address the role of oxytocmerglc pathways m the brain m the medlatlon of these responses, we mvestlgated the effects of central pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…In prior studies, OT has been shown to either increase or decrease blood pressure (21,22), which could directly affect atherosclerosis. Therefore, the effects of OT infusion on blood pressure were examined in a separate cohort of C57BL/6 mice implanted with osmotic pumps to deliver 0 μ g/kg/hr, 1 μ g/kg/hr, or 5 μ g/kg/hr OT, and blood pressure was monitored over a 2-week period.…”
Section: Methodsmentioning
confidence: 99%
“…In prior studies, OT has been shown to either increase or decrease blood pressure (21,22), which could directly affect atherosclerosis. Therefore, the effects of OT infusion on blood pressure were examined in a separate cohort of C57BL/6 mice implanted with osmotic pumps to deliver 0 μ g/kg/hr, 1 μ g/kg/hr, or 5 μ g/kg/hr OT, and blood pressure was monitored over a 2-week period.…”
Section: Methodsmentioning
confidence: 99%
“…Intracerebroventricularly injected OT decreased blood pressure, whereas inhibition of brain OT synthesis by an anti-sense oligonucleotide increased blood pressure in rats (6). In primates, humans, and rats the administration of oxytocin is often associated with a decrease in blood pressure (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the central nervous system, OT-containing axons terminate in several brain stem nuclei known to be involved in cardiovascular control, suggesting a potential role for OT in central cardiovascular regulation (3,4). Indeed, decreased blood pressure may be observed in response to oxytocin given intracerebroventricularly (5), and the inhibition of brain OT synthesis by an antisense oligonucleotide increased blood pressure in rats (6). In primates or humans, the administration of oxytocin often is associated with a decrease in blood pressure (7,8).…”
mentioning
confidence: 99%